An integrative proteome analysis of different seedling organs in tolerant and sensitive wheat cultivars under drought stress and recovery. Issue 9 (May 2015) - Hao, Pengchao; Zhu, Jiantang; Gu, Aiqin; Lv, Dongwen; Ge, Pei; Chen, Guanxing; Li, Xiaohui; Yan, Yueming
Abstract : Roots, leaves, and intermediate sections between roots and leaves (ISRL) of wheat seedlings show different physiological functions at the protein level. We performed the first integrative proteomic analysis of different tissues of the drought‐tolerant wheat cultivar Hanxuan 10 (HX‐10) and drought‐sensitive cultivar Chinese Spring (CS) during a simulated drought and recovery. Differentially expressed proteins (DEPs) in the roots (122), ISRLs (146), and leaves (163) showed significant changes in expression in response to drought stress and recovery. Numerous DEPs associated with cell defense and detoxifications were significantly regulated in roots and ISRLs, while in leaves, DEPs related to photosynthesis showed significant changes in expression. A significantly larger number of DEPs related to stress defense were upregulated in HX‐10 than in CS. Expression of six HSPs potentially related to drought tolerance was significantly upregulated under drought conditions, and these proteins were involved in a complex protein–protein interaction network. Further phosphorylation analysis showed that the phosphorylation levels of HSP60, HSP90, and HOP were upregulated in HX‐10 under drought stress. We present an overview of metabolic pathways in wheat seedlings based on abscisic acid signaling and important protein expression patterns.